Pulmonary anatomy and a case of unilateral aplasia in a common snapping turtle (Chelydra serpentina): developmental perspectives on cryptodiran lungs. Issue 6 (24th October 2017) - Schachner, E. R.; Sedlmayr, J. C.; Schott, R.; Lyson, T. R.; Sanders, R. K.; Lambertz, M.
Abstract: The common snapping turtle ( Chelydra serpentina ) is a well studied and broadly distributed member of Testudines; however, very little is known concerning developmental anomalies and soft tissue pathologies of turtles and other reptiles. Here, we present an unusual case of unilateral pulmonary aplasia, asymmetrical carapacial kyphosis, and mild scoliosis in a live adult C. serpentina . The detailed three‐dimensional (3D) anatomy of the respiratory system in both the pathological and normal adult C. serpentina, and a hatchling are visualized using computed tomography (CT), microCT, and 3D digital anatomical models. In the pathological turtle, the right lung consists of an extrapulmonary bronchus that terminates in a blind stump with no lung present. The left lung is hyperinflated relative to the normal adult, occupying the extra coelomic space facilitated by the unusual mid‐carapacial kyphotic bulge. The bronchial tree of the left lung retains the overall bauplan of the normal specimens, with some minor downstream variation in the number of secondary airways. The primary difference between the internal pulmonary structure of the pathological individual and that of a normal adult is a marked increase in the surface area and density of the parenchymal tissue originating from the secondary airways, a 14.3% increase in the surface area to volume ratio. Despite this, the aplasia has not had an impact upon the ability of the turtle to survive; however, it did interfere with aquatic locomotion and buoyancy control under water. This turtle represents a striking example of a non‐fatal congenital defect and compensatory visceral hypertrophy.